Peran Pemerintah Indonesia untuk Meningkatkan Perlindungan Hukum bagi Investor Asing Melalui Klausul Persetujuan Peningkatan dan Perlindungan Penanaman Modal (P4M) antara Indonesia - Singapura - Andanu Raditya (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The Indonesian government signed the Agreement on the Improvement and Protection of Investment (P4M) between Indonesia and Singapore to protect the rights of foreign investors in carrying out foreign investment in Indonesia. This research contains two problem formulations, namely how the role of the Indonesian government in increasing legal protection for foreign investors through legislation in Indonesia? and how the clauses in the articles of the Bilateral Investment Treaty (BIT) between Indonesia and Singapore protect foreign investors. The results of this study in addition to knowing the laws and regulations in Indonesia governing foreign investment in protecting foreign investors and clauses in the P4M Indonesia - Singapore, Furthermore, in the context of foreign investment implementation in Indonesia, this paper investigates the mechanisms by which these instruments protect the interests of foreign investors.